PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DENGAN PERSEPSI PASIEN SEBAGAI PEMEDIASI(Survei pada Pasien Rawat Inap Rumah Sakit Umum Daerah Sogaten Madiun) - Sutarno, Erlina Susilorini, Alwi Suddin & (Universitas Slamet Riyadi, 2018)
This research aims to know the influence of the quality of service to thesatisfaction of the patient's inpatient care either directly or through themediation of perception Public Hospital patients in the area Sogaten the cityof Madiun. Sample taken based on random sampling of 10% of thepopulation of 96. Engineering data collection using the questionnaire throughthe test validity and reliability. Analytical techniques through the analysis ofthe path (path) with a classic assumption test. Of the validity of the testresults, the research instrument of the variable quality of service, patientsatisfaction and patient perception. Reliability test result is reliability. From aclassic assumption test, test, test multicolinearity escape heteroscedastisitypasses test, test and qualify autocorrelation normality test passes. Theresults of the analysis show that significant effect against service qualitysatisfaction of the patient. Quality of service effect significantly to perceptionsof patients. The patient's perception of the effect significantly to patientsatisfaction. The patient does not mediate the perception of service qualitytowards the satisfaction of inpatients in a general hospital area of SogatenTown of Madiun.Keywords: Quality of Service, Patient Satisfaction, Patient PerceptionÂ